A late eocene-early Oligocene transgressive event in the Golfo San Jorge basin: Palynological results and stratigraphic implications. (November 2015) - Paredes, José M.; Foix, Nicolás; Guerstein, G. Raquel; Guler, María V.; Irigoyen, Martín; Moscoso, Pablo; Giordano, Sergio
Abstract: A new Cenozoic dataset in the subsurface of the South Flank of the Golfo San Jorge Basin (Santa Cruz province) allowed to identify a non-previously recognized transgressive event of late Eocene to early Oligocene age. Below of a marine succession containing a dinoflagellate cyst assemblage that characterizes the C/G palynological zone of the Chenque Formation (early Miocene), a 80–110 m thick marine succession contains a palynological assemblage integrated by Gelatia inflata, Diphyes colligerum and Reticulatosphaera actinocoronata supporting the occurrence of a marine incursion in the basin during the Eocene–Oligocene transition (EOT). The new lithostratigraphic unit - here defined as El Huemul Formation – covers in sharp contact to the Sarmiento Formation, and become thinner from East to West; the unit has been identified in about 1800 well logs covering up to 3500 km 2, and its subsurface distribution exceed the boundaries of the study area. The El Huemul Formation consists of a thin lag of glauconitic sandstones with fining-upward log motif, followed by a mudstone-dominated succession that coarsening-upward to sandstones, evidencing a full T-R cycle. Preservation of the El Huemul Formation in the subsurface of the South Flank has been favored by the reactivation of WNW-ESE late Cretaceous normal faults, and by the generation of N–S striking normal faults of Paleocene-Eocene age. Flexural loading associated to igneous intrusions of Paleocene?- middle Eocene age also promoted the increase of subsidence in the South Flank of the basin prior to the transgression. Graphical abstract: Highlights: A new transgression was identified in the subsurface of the Golfo San Jorge Basin. A palynological assemblage constrains the age to the Eocene-Oligocene transition. A new lithostratigraphical unit is proposed: El Huemul Formation.